Analysis of Islamic Value-Integrated Mathematics Learning: Efforts to Form Prospective Mathematics Teacher with Religious Character - Kusmaryono, Imam; Aminudin, Mohamad; Abdul Basir, Mochamad (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini menerapkan mixed methods dengan desain embedded experimental. Tujuan penelitian untuk mendeskripsikan implementasi pembelajaran matematika terintegrasi nilai Islam dalam membentuk karakter religious mahasiswa, dan menguji adanya pengaruh karakter religious dan motivasi terhadap prestasi belajar mahasiswa dalam pembelajaran matematika terintegrasi nilai Islam. Partisipan penelitian terdiri dari seorang dosen, seorang observer, dan 35 mahasiswa calon guru matematika. Pengumpulan data diperoleh melalui wawancara, angket, tes, dan observasi. Data kualitatif dianalisis secara deskriptif dan data kuantitatif dianalisis melalui uji korelasi dan ANOVA. Hasil penelitian menyimpulkan bahwa implementasi pembelajaran matematika terintegrasi nilai-nilai Islam dalam rangka mengembangkan karakter religious terdiri tiga tahap yaitu: tahap penanaman nilai, tahap implementasi, dan tahap reflection. Implementasi pembelajaran matematika terintegrasi nilai Islam telah membentuk mahasiswa memiliki karakter religious dan mampu mengingat 4 – 5 ayat Al Quran dan maknanya. Analisis inferensi menunjukkan terdapat korelasi antara variable religious charater dan motivation terhadap prestasi belajar. Ketiga variable memiliki hubungan searah (positif). Hal ini berarti, apabila religious charater dan motivation semakin tinggi maka prestasi belajar semakin tinggi (mengalami kenaikan). Secara simultan variable karakter religious dan motivasi berpengaruh signifikan terhadap variable prestasi belajar. This study applies mixed methods with an embedded experimental design. The research objectives were to describe the implementation of Islamic values integrated mathematics learning in shaping students' religious character, and examine the influence of religious character and motivation on student achievement in learning mathematics integrated with Islamic values. The research participants consisted of a lecturer, an observer, and 35 students. Data collection was obtained through interviews, questionnaires, tests, and observation. Qualitative data were analyzed descriptively and quantitative data were analyzed through correlation tests and ANOVA. The results of the study concluded that the implementation of integrated mathematics learning with Islamic values in order to develop religious character consisted of three stages, namely the value instillation stage, the implementation stage, and the reflection stage. The implementation of learning mathematics integrated with Islamic values has formed students who have religious character and are able to remember 4-5 verses of the Koran and their meanings. Inference analysis shows that there is a correlation between religious character and motivation variables on learning achievement. The three variables have a unidirectional (positive) relationship. This means, if the religious character and motivation are higher, the learning achievement will be higher (increase). Simultaneously the variables of religious character and motivation have a significant effect on the learning achievement variable.